Proceso de atención de enfermería en gestante de 23 años con embarazo de 22 semanas más amenaza de aborto y anemia. - Aguirre Palma, Johanie Priscila (2020)
During the gestation period, different pathologies may appear that lead to putting the lives of the mother and the child at risk. The threat of abortion is one of the best known causes of high severity. arriving at the emergency area. Anemia is the most common nutritional disorder in the world, due to the high demand for iron in pregnancy. The purpose of the present clinical case is to present the nursing care process in a 23-year-old pregnant woman with 22 weeks who attends the Guasmo Sur General Hospital, due to presenting a clinical picture of ± 24 hours of evolution which presented clinical manifestations with loss of mucus and blood in little quantity. The nursing care process was based on the direct care function of the patient, therefore the interventions were developed based on the needs of the pregnant woman. Resulting in the creation of nursing tools based on Nanda, Noc and Nic. To provide the patient with quality and warm care.